Adoption of land uses compatible with the water ecosystem service in agricultural farms in Central America - Meza, Víctor (2013)
The presence of trees in the farms is typically considered a good practice in water shed  management. Therefore, it was examined the voluntary adoption of land uses considered more compatible with the water ecosystem service (shade coffee and woodland) in the region of Trifinio (located in Honduras and Guatemala), where there is not given any incentives or payment for this environmental service. It was observed low adoption of these land uses on small farms. In practice, participation of small farms in conservation programs are subject to certain factors beyond the control of the producers such as minimum area of the farm. But, other factors such as perceived importance of land use has on food security and future motivation for adopting a production system can be more easily manipulated, although, in practical terms it is not always possible. Thus, for a spontaneous adoption of the trees and the forest should also influence cultural factors, even if the changes in this dimension generally take longer to be observed than the lifetime of the conservation projects.